Effect of Annealing Temperature on the Structural and Morphological Properties of Silver Nano Layers Deposited on Copper Oxide - Maedeh, Khodadadi; Bagher, Askari Mohammad; Sedigheh, Bagheri (International Journal of Chemistry and Materials Research, 2015)
In this investigation in the first step, the Cu thin films have been deposited on silicon substrates by means of DC magnetron sputtering method in fixed conditions.Then, for preparation of CuO thin films the thermal oxidation of Cu films under the oxygen flow at 300ºC for 4 h were done in electrical furnace.In the second step the Ag thin films have been deposited on CuO thin films by means of DC magnetron sputtering method in fixed conditions. Then they have been annealed at different temperatures such as 100°C, 200°C and 300°C for 4 hours. The effect of annealing temperatures on the structural and morphological properties of the films was investigated by different analysis, such as X-ray diffraction (XRD) and atomic force microscope (AFM). The XRD analysis showed three peaks belongs to Ag (111), Ag2O (200) and CuO (-111).The AFM analysis exhibited that, annealing temperature influenced the surface morphology of the films.